Modernism: The Creation of Nation-States - Ahmet Ersoy, Maciej Górny, Vangelis Kechriotis (Central European University Press, 2010)
This is the first part of the third volume of the four-volume series, a daring project of CEU Press, presenting the most important texts that triggered and shaped the processes of nation-building in the many countries of Central and Southeast Europe. The aim is to confront 'mainstream' and seemingly successful national discourses with each other, thus creating a space for analyzing those narratives of identity which became institutionalized as "national canons." This is the first part of the...